2021
DOI: 10.3390/microorganisms9020276
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Functionally Related Gene Clusters in the Opportunistic Pathogen, Candida albicans

Abstract: The proper balance of gene expression is essential for cellular health, organismal development, and maintaining homeostasis. In response to complex internal and external signals, the cell needs to modulate gene expression to maintain proteostasis and establish cellular identity within its niche. On a genome level, single-celled prokaryotic microbes display clustering of co-expressed genes that are regulated as a polycistronic RNA. This phenomenon is largely absent from eukaryotic microbes, although there is ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Systematic analysis of the incidence of functional clustering of metabolically related groupings defined by gene ontology designations found that the grouping of members into pairings was a feature of many gene families in S. cerevisiae (27% of all families exhibited a statistically significant incidence of clusters) [59]. An extension of this analysis to the more distantly related C. albicans revealed the same results, in spite of the evolutionary distance-and drastically different lifestyles-between these two species [60]. One surprising discovery was that, although a similar phenomenon was observed, the actual members that comprised the pairings were different between the species.…”
Section: Within Dikarya Study Of Ascomycetes Has Yielded Complex Insi...mentioning
confidence: 61%
“…Systematic analysis of the incidence of functional clustering of metabolically related groupings defined by gene ontology designations found that the grouping of members into pairings was a feature of many gene families in S. cerevisiae (27% of all families exhibited a statistically significant incidence of clusters) [59]. An extension of this analysis to the more distantly related C. albicans revealed the same results, in spite of the evolutionary distance-and drastically different lifestyles-between these two species [60]. One surprising discovery was that, although a similar phenomenon was observed, the actual members that comprised the pairings were different between the species.…”
Section: Within Dikarya Study Of Ascomycetes Has Yielded Complex Insi...mentioning
confidence: 61%
“…Moreover, the expansion of gene families has been detected among these fungal species [6]. It was also reported that spatial organization allows for position effects to stabilize RNA expression and balance transcription, which can be advantageous for a number of reasons, including reductions in stochastic influences between the gene products and the organization of co-regulated gene families into functional clusters occurs extensively in Dikarya fungi [7][8][9]. The functionally clustered genes localize to genomic loci that are more conducive to transcriptional regulation at a distance compared to the unpaired members of the same families in Saccharomyces cerevisiae [10,11].…”
Section: Introductionmentioning
confidence: 98%